PONDASI FILOSOFIS KEBEBASAN DAN DEMOKRASI - Abdul Hasib (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to determine and analyze the effect of market orientation and innovation on business performance with competitive advantage as an intervening variable (a case study of salted egg UMKM in Brebes district). This study used a quantitative research type with the research sample calculated using total sampling technique and obtained a total sample of 50 respondents. Data collection techniques using a questionnaire. Data analysis used linear regression analysis. Market orientation partially has a positive and significant effect on business performance in salted egg SMEs in Brebes Regency. The research results show that Innovation partially has no effect on business performance in salted egg SMEs in Brebes Regency. Market orientation partially has a positive and not significant effect on competitive advantage in salted egg SMEs in Brebes Regency. Innovation partially has a positive and significant effect on competitive advantage in salted egg SMEs in Brebes Regency. Competitive advantage partially has a positive and significant effect on business performance in salted egg SMEs in Brebes Regency. Market orientation using the Sobel model 1 test has a greater effect on business performance through competitive advantage in salted egg SMEs in Brebes Regency. Innovation in the Sobel model 2 test does not have a greater effect on business performance through competitive advantage in salted egg SMEs in Brebes Regency.